The low self-efficacy trap: why people with vulnerabilities experience prolonged periods with payment problems - Kempson, Elaine; Poppe, Christian (Frontiers in Behavioral Economics, 2024)
Societies place a responsibility on individuals to pay what they owe on time, establishing a coercive apparatus for debt collection and enforcement when they do not, coupled with consumer protection and debt resolution measures to protect the vulnerable. Yet vulnerable people are unable to exercise the personal responsibility society places on them and can face prolonged periods of payment difficulties. This article seeks to understand why this occurs by applying Bandura's Social Cognitive Theory and focusing on the role that self-efficacy plays. It shows that problems primarily arise in encounters with inflexible and bureaucratic routines -of creditors, debt enforcement agents and even money advisers whose role it is to help vulnerable people -which systematically undermine defaulters' self-efficacy, leaving them in limbo.